Short- and long-term oncological outcome after rectal cancer surgery: a systematic review and meta-analysis comparing open versus laparoscopic rectal cancer surgery - Nienhüser, Henrik; Heger, Patrick; Kulu, Yakup; Diener, Markus K.; Klose, Johannes; Schneider, Martin; Müller, Beat P.; Ulrich, Alexis; Büchler, Markus W.; Mihaljevic, André Leopold; Schmidt, Thomas (Journal of gastrointestinal surgery, 2018)
While several trials have compared laparoscopic to open surgery for colon cancer showing similar oncological results, oncological quality of laparoscopic versus open rectal resection is not well investigated.